2011
DOI: 10.1111/j.1095-8312.2011.01748.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme, continuous variation in an island snail: local diversification and association of shell form with the current environment

Abstract: On Rosemary Island, a small continental island (11 km 2 ) in the Dampier Archipelago, Western Australia, snails of the genus Rhagada have extremely diverse morphologies. Their shells vary remarkably in size and shape, with the latter ranging from globose to keeled-flat, spanning the range of variation in the entire genus. Based primarily on variation in shell morphology, five distinct species are currently recognized. However, a study of 103 populations has revealed continuity of shell form within a very close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 35 publications
3
56
0
1
Order By: Relevance
“…Studies of land snails elsewhere have shown that even within a genus, shell morphology of the species has a clear relationship with habitat use (Cameron and Cook 1989;Chiba 2004;Stankowski 2011). For instance, high-spired shells are generally associated with vertical services and flat shells with horizontal surfaces (Barker 2001).…”
Section: Patterns In Composition Of the Generamentioning
confidence: 99%
“…Studies of land snails elsewhere have shown that even within a genus, shell morphology of the species has a clear relationship with habitat use (Cameron and Cook 1989;Chiba 2004;Stankowski 2011). For instance, high-spired shells are generally associated with vertical services and flat shells with horizontal surfaces (Barker 2001).…”
Section: Patterns In Composition Of the Generamentioning
confidence: 99%
“…This variation has evolved within a very short period of time on Rosemary Island; probably post-Pleistocene. Variation between the two morphological extremes occurs over a distance of less than 200 m and is strongly associated with changes in the habitat (from rocky to sandy), suggesting that the shell shape is of high adaptive significance (Stankowski 2011). The Rosemary Island case proves that dramatic changes in shell morphology may occur in short evolutionary time spans if selection is strong.…”
Section: Discussionmentioning
confidence: 96%
“…In accordance with their extensive ranges, Rhagada species may be associated with a large variety of habitats, from monsoonal vine thickets to xeric habitats, such as sandy plains dominated by spinifex grasses (Triodia spp.) or more complex, rocky outcrops with shrubby vegetation (Stankowski 2011;Johnson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these differences are well within the range of variation seen within other species. For example, detailed study of Rhagada in the Dampier Archipelago showed that much larger differences in shell form need not indicate reproductively isolated species (Stankowski 2011). The high genetic similarities and the phylogenetic interspersion of COI haplotypes indicate that Q. barrowensis is the same species as Q. montebelloensis.…”
Section: Discussionmentioning
confidence: 99%